Formulation, Evaluation, And In Vitro Antifungal Assessment of A Topical Preparation Using Leaf Extract From Tridax Procumbens L. - Saroj Yadav; Kamal Kishor Upadhyay; Praveena R; Senthil Rajan Dharmalingam; Nasreen Sulthana; Amit Kumar Singh; Sudhahar Dharmalingam; Raj K. Keservani (Revista Electronica de Veterinaria, 2024)
Background and Objectives: Most of the time, these fungi affect the skin and cause skin conditions like eczema, rashes, candidiasis, tinea pedis, and tinea corporis. Fungal diseases, which have become a major problem, can be caused by many different types of fungi. The study's goal was to create a safe and effective antifungal cream that uses Tridax procumbens L. leaf extract.Material and Methods: To make the ethanolic extract, the Soxhlet device was used. Molecular docking studies and phytochemical analyses were done on the product. The oil-in-water emulsion method was used to make the cream. A microbial culture (MIC) was done with agar dilution, and the antifungal activity of the cream against Candida albicans was tested with agar diffusion.Results: The current study shows that the leaf extract of T. procumbens has strong antifungal activity against the chosen fungus strain C. albicans. When compared to similar commercial topical treatments, the cream formulation that contained T. procumbens leaf extract was more effective at killing the test organism. Because it contains a lot of different chemicals that are thought to work in different ways against different targets, T. procumbens leaf extract and its cream form could be used instead of synthetic drugs to treat skin infections because they work just as well, are less harmful, and are less likely to lead to drug resistance.Conclusion: This study concludes that the topical formulation of T. procumbens extract exhibits possible antifungal efficacy.